KESEPADANAN TERJEMAHAN TRANSKRIP VIDEO DARI BAHASA INGGRIS KE BAHASA INDONESIA PADA MATA KULIAH MOVIE TRANSLATION (SUBTITLING) - Nurul Fitriani; Yoga Pratama; Kurnia Idawati; Alia Afiyati (Inteligensi : Jurnal Ilmu Pendidikan, 2020)
Nowadays, people can easily access everything with one-click away. For example, when you want to read an article in foreign language which you are not familiar with, then you just need to open Google Translate and within seconds, you will get the translation of it. To deal with that reality, a translator has to differentiate himself from machine translation which is increasingly used by the public. Therefore, the translator is required to produce an equivalent and natural translation in the Target Language. This research aims to provide understanding of translation equivalence on video transcripts conducted by students in Movie Translation (Subtitling) course. This study uses qualitative approach, content analysis method, and purposive sampling to collect data. In short, there are two types of translation equivalence used by students, formal and dynamic. Formal equivalence focuses on the similarity of the form and meaning of the message from Source Language to Target Language, while dynamic one focuses on the naturalness of expression in the Target Language.